The trauma signature of 2016 Hurricane Matthew and the psychosocial impact on Haiti - Shultz, James M. (Disaster Health, 2016)
Background. Hurricane Matthew was the most powerful tropical cyclone of the 2016 Atlantic Basin season, bringing severe impacts to multiple nations including direct landfalls in Cuba, Haiti, Bahamas, and the United States. However, Haiti experienced the greatest loss of life and population disruption. Methods. An established trauma signature (TSIG) methodology was used to examine the psychological consequences of Hurricane Matthew in relation to the distinguishing features of this event. TSIG analyses described the exposures of Haitian citizens to the unique constellation of hazards associated with this tropical cyclone. A hazard profile, a matrix of psychological stressors, and a “trauma signature” summary for the affected population of Haiti - in terms of exposures to hazard, loss, and change - were created specifically for this natural ecological disaster. Results. Hazard characteristics of this event included: deluging rains that triggered mudslides along steep, deforested terrain; battering hurricane winds (Category 4 winds in the “eye-wall” at landfall) that dismantled the built environment and launched projectile debris; flooding “storm surge” that moved ashore and submerged villages on the Tiburon peninsula; and pummeling wave action that destroyed infrastructure along the coastline. Many coastal residents were left defenseless to face the ravages of the storm. Hurricane Matthew's slow forward progress as it remained over super-heated ocean waters added to the duration and degree of the devastation. Added to the havoc of the storm itself, the risks for infectious disease spread, particularly in relation to ongoing epidemics of cholera and Zika, were exacerbated. Conclusions. Hurricane Matthew was a ferocious tropical cyclone whose meteorological characteristics amplified the system's destructive force during the storm's encounter with Haiti, leading to significant mortality, injury, and psychological trauma.